Harnessing the Membrane Translocation Properties of AB Toxins for Therapeutic Applications - Numa Piot; F. Gisou van der Goot; Oksana A. Sergeeva (Toxins, 2021)
Over the last few decades, proteins and peptides have become increasingly more common as FDA-approved drugs, despite their inefficient delivery due to their inability to cross the plasma membrane. In this context, bacterial two-component systems, termed AB toxins, use various protein-based membrane translocation mechanisms to deliver toxins into cells, and these mechanisms could provide new insights into the development of bio-based drug delivery systems. These toxins have great potential as therapies both because of their intrinsic properties as well as the modular characteristics of both subunits, which make them highly amenable to conjugation with various drug classes. This review focuses on the therapeutical approaches involving the internalization mechanisms of three representative AB toxins: botulinum toxin type A, anthrax toxin, and cholera toxin. We showcase several specific examples of the use of these toxins to develop new therapeutic strategies for numerous diseases and explain what makes these toxins promising tools in the development of drugs and drug delivery systems.